2008
DOI: 10.1093/ije/dyn051
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in health by social class dimensions in European countries of different political traditions

Abstract: This study is one of the first to show the impact of different political traditions on social class inequalities in health. These results emphasize the need to evaluate the impact of the implementation of public policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
76
1
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 32 publications
7
76
1
6
Order By: Relevance
“…In this respect, our findings are in keeping with the broader literature, as the Bismarckian and Southern regimes fairly consistently exhibited smaller educational inequalities in health across most age groups and among both men and women. Various studies of self-rated health and mortality have come to the same conclusion (10)(11)(12)14). Our results, therefore, like those in earlier studies, are very challenging in terms of theorizing the relationship between welfare state inputs and health inequalities outputs.…”
Section: Discussionsupporting
confidence: 62%
“…In this respect, our findings are in keeping with the broader literature, as the Bismarckian and Southern regimes fairly consistently exhibited smaller educational inequalities in health across most age groups and among both men and women. Various studies of self-rated health and mortality have come to the same conclusion (10)(11)(12)14). Our results, therefore, like those in earlier studies, are very challenging in terms of theorizing the relationship between welfare state inputs and health inequalities outputs.…”
Section: Discussionsupporting
confidence: 62%
“…Research using the European Social Survey found no difference in the likelihood of reporting poor self-reported health across conservative, social democratic, and liberal welfare regimes (7,26,68). Relative health inequalities related to SES were not smaller in social democratic regimes nor consistently larger in liberal regimes (7,8,25,27,29,87). Income-and education-related health inequalities were smallest in conservative regimes and highest in social democratic regimes for education (27) and in liberal regimes for income (25,87) and unemployment (7).…”
Section: Welfare-state Regimes and Healthmentioning
confidence: 94%
“…We further hypothesize that the social gradient will be more pronounced in Spain compared with Denmark. This second hypothesis is, among other things, motivated by the fact that Denmark has much lower organizational power distance than Spain [20] and that research has shown wider health inequalities in late democracies (such as Spain) compared to countries with a long tradition of social democracy (such as Denmark) [21].…”
mentioning
confidence: 99%